Estudo das propriedades estruturais, magnéticas, eletrônicas e ópticas das manganitas multiferróicas LuMnO3 e HoMnO3 via cálculos baseados em non-collinear spin DFT - Brito, Douglas Meneses Santos (2022)
In this work, structural, electronic, magnetic, and optical properties of the hexagonal LuMnO3 and HoMnO3 multiferroic compounds were studied. These materials with P63cm crystallographic space group (ferroelectric phase) gained attention of researchers because of their magnetoelectric coupling below the Néel temperature (TN < 90 K in the case of LuMnO3 and TN < 72 K in the case of HoMnO3). In this condition, these materials can be applied in new technologies in the spintronic field. The present study was carried out through calculations based on Non-collinear Spin Density Functional Theory using the All-electron Full-Potential Linearized Augmented Plane Wave electronic structure method implemented in the Elk computational code. The exchange and correlation electronic effects were considered in the framework of Local Spin Density Approximation including the effective Hubbard (Ueff) correction. The general objective of the thesis work was to contribute to the elucidation of divergent results in the literature on some of the structural, electronic, magnetic and optical properties of LuMnO3 and HoMnO3. For the first time in the literature, the combination of calculation methods described above was applied to investigate the aforementioned properties of LuMnO3 and HoMnO3. In the case of LuMnO3, the results reveal that the P63cm crystallographic space group with the Γ3 + Γ4 magnetic structure (o = 80°) should be the ground state of the material. Based on these results, the electronic band structure, the effective mass tensor of the charge carriers (electrons and holes), density of states, and the dielectric tensor of the material were calculated. The results were compared and discussed with those in the literature. The energy band gap value of 1.2 eV agrees very well with that predicted from optical conductivity measured (1.1 eV). In the case of HoMnO3, the magnetic structure of the ground state was determined and, based on it, the electronic and optical properties were calculated. The HoMnO3 calculations showed that the material has a non-collinear magnetic structure for both Ho3+ and Mn3+ ions sublattices. The magnetic configuration in the Mn3+ ion sublattice agrees with the results predicted by some experimentalists. However, in the case of the Ho3+ ion sublattice, the results are different from those predicted in the literature. The calculated energy band gap was 1.25 eV. This result agrees very well with what was experimentally predicted (1.4 eV). In addition, the material presents values charge carriers effective mass similar to LuMnO3. This characteristic of HoMnO3, together with other fundamental properties similar to that of LuMnO3, allows us to conclude that HoMnO3 exhibits potential as a photoferroic material.